Survey on sarcophagidae species at a poultry farm in Hulu Langat, Selangor - Mohd Isa, Mohamad Khairulanuar (2016)
A survey of flies was conducted at a poultry farm in Hulu Langat, Selangor. A total of 2,037 flies specimens were collected which comprised of member of Calliphoridae (296.5±40.7), Muscidae (27.0±10.2) and Sarcophagidae (16.2±6.1). Mean number of flies captured in the morning session was 390.0±92.9 while a lower mean number of flies was recorded (289.0±59.9) in the evening session. Calliphoridae flies recorded the highest catch in both morning (323.0±69.0) and afternoon session (270.0±52.9), followed by Muscidae (44.7±10.8 and 9.3±2.2) and Sarcophagidae (22.3±14.2 and 9.7±4.9). The population of flies did not show significant different between the sampling times except for Muscidae flies. Flies from the three families were found abundant in the vacant area than the dumping area and feeding area. However, the mean number of flies from the three families recorded in these sampling areas did not show significant difference. Three sampling methods were used for sampling, the net bottle bait trap captured the highest number of specimens, followed by handpicking method and aquarium method. The net bottle bait trap could trap 4 times and 1 time more Calliphoridae than the handpicking and aquarium methods respectively. It also trapped 4 times and 30 times more Muscidae and Sarcophagidae than other methods. A detail study was carried out on the genus of Sarcophagidae flies. This family comprised of Amobia erythrura, Sarcophaga dux, Sarcophaga misera, Sarcophaga princeps and Sarcophaga taenionota which were confirmed by morphological and C0II gene identification. These species had scored 100% bootstrap percentage value when compared to other reference species in the GenBank. Among the Sarcophagidae species, S. dux was abundant (5.8±2.3) in the poultry farm, followed by S. princeps (5.0±1.8), S. misera (2.5±1.2), S. taenionota (2.5±1.1) and A. erythrura (0.2±0.2). It also scored the highest mean number of specimen captured in both morning and afternoon sessions at different sampling areas using different sampling methods. S. princeps became the second abundant fly and A. Erythrura became the least abundant fly recorded in all parameters tested. No significant different was found among the Sarcophagidae flies when sampling at different sampling times with different sampling areas. The handpicking method was the best sampling method to capture Sarcophagidae species. Calliphoridae, Muscidae and Sarcophagidae are reported to have transmitted diseases to domesticated animals and human. Control measure should be taken as these flies were found easily in the poultry farm.